1998
DOI: 10.1063/1.121593
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and structural defects in erbium-implanted silicon annealed at high temperature

Abstract: The behavior of luminescence spectra and structural defects in single crystal Czochralski silicon after erbium implantation at 1 MeV energy and 1×1013 cm−2 dose with subsequent annealing at 1100 °C for 0.25–3 h in an argon or chlorine-containing ambience was studied by photoluminescence (PL), transmission electron microscopy, and chemical etching/Nomarski microscopy. We have found that annealing in the chlorine-containing ambience gives rise to dislocation loops and pure edge dislocations with dominant disloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
14
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 12 publications
7
14
0
2
Order By: Relevance
“…20 Some other studies, such as inducing super saturation of non-equilibrium self-interstitials by ion implantation forming a silicon layer in which compression stresses appeared, also shown the strong D1/D2 luminescence. 34 On the other hand, during the high temperature annealing, oxygen atoms could diffuse quickly and get gathered at dislocations in CZ silicon, 35 which is also confirmed by the FTIR results in our case. Fedina et al 33 found significant D1/D2 lines in the sample whose dislocations are caused by O þ implantation, but no DRL signals in the B þ implanted samples, even after thermal annealing.…”
Section: -supporting
confidence: 84%
“…20 Some other studies, such as inducing super saturation of non-equilibrium self-interstitials by ion implantation forming a silicon layer in which compression stresses appeared, also shown the strong D1/D2 luminescence. 34 On the other hand, during the high temperature annealing, oxygen atoms could diffuse quickly and get gathered at dislocations in CZ silicon, 35 which is also confirmed by the FTIR results in our case. Fedina et al 33 found significant D1/D2 lines in the sample whose dislocations are caused by O þ implantation, but no DRL signals in the B þ implanted samples, even after thermal annealing.…”
Section: -supporting
confidence: 84%
“…Sobolev et al [14] find the directly measured decay time for D1 in deliberately dislocated erbium-implanted silicon is 50µs, which is close that of the fast decays in this work.…”
Section: Results and Discussion: Optical Characterisationsupporting
confidence: 61%
“…The capture cross section is proportional to the slope of this data (equation (3)) and therefore this confirms that the apparent 14 capture cross section, if it could be measured, is decreasing with fill pulse time. This is indicative of an energy state(s) becoming more repulsive to further capture as the experimental time progresses, i.e.…”
Section: Results and Discussion: Electrical Characterisationsupporting
confidence: 54%
See 1 more Smart Citation
“…Их природа окончательно не установлена до сих пор, а механизм образования центров D1 и D2 в случае деформации образцов методом четырехточечного изгиба, т. е. при достаточно низкой плотности дислокаций и достаточно низких температурах, может отличаться от механизмов, реализуемых при других методах введения дислокаций. Как показано в [12], в случаях термического отжига имплантированного кремния при высокой температуре в условиях пересыщения кремния собственными межузельными атомами [12] или эпитаксиального роста слоев SiGe на пластине Si [13] сначала образуются петли Франка, затем часть этих петель преобразуется в совершенные призматические дислокационные петли, а многократные пересечения совершенных петель приводят к образованию трехмерной цепочки с высокой плотностью чисто краевых дислокаций (pure edge dislocations), которые и связаны с линией D1. Недавно были получены экспериментальные данные, уточняющие связь линий D1 и D2 с конкретными структурными дефектами при отжиге имплантированных образцов [14].…”
unclassified